Perspectives of mothers and primary caregivers on undernutrition in children under 5 years in the Northwest region of Cameroon: a community based cross-sectional study - J. Eyong, Ndohtabi; Navti, Lifoter K.; Atanga, Mary B. S. (International Journal Of Community Medicine And Public Health, 2024)
Background: Cameroon is one of the sub-Saharan African countries where undernutrition is a significant public health concern, with a national prevalence of 29% among children under five. The Northwest Region of Cameroon in particular, faces a triple burden of undernutrition, with high rates of stunting (32%), wasting (6.5%) and underweight (17.2%). Caregivers play a critical role in the management of undernutrition. This study analyzed their knowledge, attitudes and predictors of knowledge levels on undernutrition. Methods: A community-based cross-sectional study was carried out among 1279 mothers and primary caregivers of under five children from six health districts. Data on their knowledge and attitudes towards undernutrition was collected using a pre-tested questionnaire. Binary logistic regression analysis was used to identify predictors of nutrition knowledge levels. Results: Overall, 78.5% of the caregivers had ‘good knowledge’ on undernutrition and 21.7% had ‘poor knowledge’. Correct knowledge was highest on the causes of undernutrition and incorrect knowledge was highest on prevention of undernutrition in children especially as 32.9% didn’t know that exclusive breastfeeding could prevent undernutrition in children below six months. Regarding attitude, 52.2% had a ‘positive attitude’ and 47.7% had a ‘less positive or negative attitude’. The main predictors of knowledge levels among primary caregivers were sex of carer (p=0.001), household size (p=0.001), religion (p=0.010), residence status (p<0.001), occupation (p<0.001), and degree of urbanization (p=0.002). Conclusions: Caregivers in Northwest Cameroon showed good undernutrition knowledge (78.5%), but lacked knowledge on prevention, especially breastfeeding benefits. Sociodemographic factors influenced knowledge. This could inform interventions to improve practices.